A software framework for data based analysis - Markus Krätzig (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2005)
This paper presents the software framework JStatCom which is geared towards the development of rich GUI clients for numerical procedures. The concept is to solve all recurring tasks with the help of reusable Java components. Optionally, one can delegate the execution of special numerical algorithms to external programs, for example Gauss or Matlab. This way it is possible to reuse an already existing code base for numerical routines written in different programming languages and to link them with the Java world. A reference application for JStatCom is the econometric software package JMulTi, which will shortly be introduced.
Keywords: 330; Java; Object-Oriented Programming; Econometrics; Software Engineering; Zeitreihenanalyse; Ökonometrie; PC-Software